Pola Asosiasi Flora pada Area Terdampak Invasi Derris trifoliata di Kawasan Hutan Mangrove - Sanira Sari; Syaiful Eddy; Dewi Rosanti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Mangrove ecosystems in the Air Telang Protected Forest are experiencing ecological pressure due to the dominance of the liana Derris trifoliata, which has the potential to alter the structure of vegetation communities. This study aimed to analyze the patterns of floral associations in mangrove areas affected by the dominance of Derris trifoliata. The study employed a descriptive survey method with a purposive sampling approach across four observation stations. Species association analysis was conducted using the Jaccard Index based on species presence data. The results identified 34 plant species associated with Derris trifoliata, consisting of ferns, monocots, and dicots, indicating a heterogeneous vegetation community. Similarity values among stations ranged from 0.154 to 0.594, with the highest similarity observed between Stations 2 and 3, and the lowest between Stations 2 and 4. The association values between Derris trifoliata and other species ranged from 0.25 to 1.00, with a very high association found in Nypa fruticans and a high association in Acrostichum aureum. The dominance of neutral associations indicates ecological pressure that tends to simplify the structure of mangrove vegetation communities. Ecologically, the presence of Derris trifoliata plays a role in shaping species distribution patterns through interactions influenced by environmental heterogeneity and mangrove habitat conditions.